The Influence of the Distributor Plate on the Bottom Zone of a Fluidized Bed Approaching the Transition from Bubbling to Turbulent Fluidization - Paiva, J. M. (2004)
The dynamics of the bottom zone of a narrow fluidized bed, from bubbling to turbulent regimes, was studied in a cold model of 0.1 m i.d. and 1.3 m high. Tested distributor types were perforated perspex plates, with six different perforation grids, metallic mesh and porous ceramic, with pressures drops ranging from 0.05 to 350 kPa, corresponding to superficial air velocities from 0.1 to 2.3m s-1. Group B silica ballotini, within the range 0.355-0.425 mm, were used as bed material. The experimental data consisted of pressure drop and absolute pressure fluctuating signals, together with visual observations. The bottom zone presented a dynamic condition that produced higher pressure drop values than those expected with the incipient fluidization condition, particularly for the distributor plates with a higher open area. A simple model is used to describe the axial solids distribution and the dynamics characteristics of the voids created in that zone, and an attempt is made to differentiate the bubble voidage from that of the dense phase, with a value of through flow estimated in a systematic way.